Electrophysiological Examination of Feedback-Based Learning in 8–11-Year-Old Children - Arbel, Yael; Fox, Annie B. (Frontiers in Psychology, 2021)
The study aimed at evaluating the extent to which the feedback-related negativity (FRN), an ERP component associated with feedback processing, is related to learning in school-age children. Eighty typically developing children between the ages of 8 and 11 years completed a declarative learning task while their EEG was recorded. The study evaluated the predictive value of the FRN on learning retention as measured by accuracy on a follow-up test a day after the session. The FRN elicited by positive feedback was found to be predictive of learning retention in children. The relationship between the FRN and learning was moderated by age. The P3a was also found to be associated with learning, such that larger P3a to negative feedback was associated with better learning retention in children.